Engineering characterisation of epoxidized natural rubber-modified hot-mix asphalt - Al-Mansob, R.A.; Ismail, A.; Yusoff, N.I.M.; Rahmat, R.A.O.K.; Borhan, M.N.; Albrka, S.I.; Azhari, C.H.; Karim, M.R. (Public Library of Science, 2017)
Road distress results in high maintenance costs. However, increased understandings of asphalt behaviour and properties coupled with technological developments have allowed paving technologists to examine the benefits of introducing additives and modifiers. As a result, polymers have become extremely popular as modifiers to improve the performance of the asphalt mix. This study investigates the performance characteristics of epoxidized natural rubber (ENR)-modified hot-mix asphalt. Tests were conducted using ENR±asphalt mixes prepared using the wet process. Mechanical testing on the ENR±asphalt mixes showed that the resilient modulus of the mixes was greatly affected by testing temperature and frequency. On the other hand, although rutting performance decreased at high temperatures because of the increased elasticity of the ENR±asphalt mixes, fatigue performance improved at intermediate temperatures as compared to the base mix. However, durability tests indicated that the ENR±asphalt mixes were slightly susceptible to the presence of moisture. In conclusion, the performance of asphalt pavement can be enhanced by incorporating ENR as a modifier to counter major road distress.